Non-coding RNA Contribution to Thoracic and Abdominal Aortic Aneurysm Disease Development and Progression - Li, Yuhuang; Maegdefessel, Lars (Frontiers in Physiology, 2017)
Multiple research groups have started to uncover the complex genetic and epigenetic machinery necessary to maintain cardiovascular homeostasis. In particular, the key contribution of non-coding RNAs (ncRNAs) in regulating gene expression has recently received great attention. Aneurysms in varying locations of the aorta are defined as permanent dilations, predisposing to the fatal consequence of rupture. The characteristic pathology of an aneurysm is characterized by progressive vessel wall dilation, promoted by dying vascular smooth muscle cells and limited proliferation, as well as impaired synthesis and degradation of extracellular matrix components, which at least partially is the result of transmural inflammation and its disruptive effect on vessel wall homeostasis. Currently no conservative pharmacological approach exists that could slow down aneurysm progression and protect from the risk of acute rupture. In the recent past, several non-coding RNAs (mainly microRNAs) have been discovered as being involved in aneurysm progression throughout varying locations of the aorta. Exploring ncRNAs as key regulators and potential therapeutic targets by using antisense oligonucleotide strategies could open up promising opportunities for patients in the near future. Purpose of this current review is to summarize current findings and novel concepts of perspectivly utilizing ncRNAs for future therapeutic and biomarker applications.